Filosofía y literatura: una experiencia de encuentro con la infancia (2016)
The article presents some of the results of the macro project called philosophy and childhood: research and possibilities of innovation in the rural schools, specifically, in the implementation and systematization of an experience that proposes an encounter among childhood, philosophy and literature. This happens In a Rural School called Leonera in a small town called Toca in the Department of Boyacá. “ A way to come “ makes reference to the methodological orientations that guided the research process. “To occupy a school “makes sense to the place in the voice of the same children. The results at the beginning present a new view of the concepts of childhood, literature and philosophy. A point of meeting which invites the constitution to questions and dialogues as a way of life. Literary fabric is shared from indigenous texts, which are demonstrations of the researchers and some children. The end of the article is an analysis of some thoughts around this meeting.